Synthesis and biological properties of hemin conjugates with unprotected peptides. - S. A. Okorochenkov; E. A. Bistrova; E. M. Pavlova; G. A. Zheltukhina; V. E. Nebolsin (Тонкие химические технологии)
Arginine-containing peptides consisted of 3- and 13- amino acids residues, namely RGD and [5Ala]-indolicidine were synthetized. Monosubstituted hemin derivatives modificated by RGD, [5Ala]-indolicidine and gramicidine S were obtained. Biocide activity and low toxicity of obtained conjugates was shown.